Synthesis and characterization of ZnAl-layered double hydroxide and organo-K10 montmorillonite for the removal of diclofenac from aqueous solution - Nadia Boukhalfa; Mokhtar Boutahala; Nassima Djebri (Adsorption Science & Technology)
Two prepared adsorbents, namely, calcined ZnAl-layered double hydroxide and K10 montmorillonite intercalated with cetyltrimethyl-ammonium bromide cations are used in diclofenac sodium adsorption under the batch reactor operations. The pseudo-second-order model describes better the results of the kinetics. Fitting parameters revealed that the rate of adsorption increased with the increase in diclofenac sodium concentration and decrease in background electrolyte concentration and temperature, while the solution pH did not have a significant effect. The maximum adsorption capacities of diclofenac obtained by Langmuir model are found to be 55.46 and 737.02 mg/g for K10 montmorillonite intercalated with cetyltrimethyl-ammonium bromide cations and ZnAl-C LDH, respectively. The results of adsorption–desorption cycles revealed that ZnAl-C LDH and K10 montmorillonite intercalated with cetyltrimethyl-ammonium bromide cations have an excellent potential to be used as an economical adsorbent for the removal of diclofenac sodium from water.